Effect of Black Cumin on the Expression of Genes Related to Lipid Metabolism in Adipose Tissue: A Mouse Model Study - Roya Maleki; Ali Ahadi; Hoda Ayat (Journal of Genetic Resources, 2024)
Obesity, as a complex multifactorial disease, can be considered as a suitable goal for treatment by traditional medicine. This study aimed to investigate the effect of black cumin on the expression of some important genes in the metabolism of lipids. For this purpose, 14 male Balb/c mice were divided into control and treatment groups. Mice in the control group were fed standard food, and mice in the treatment group were fed with a mix containing 50% standard food and 50% powdered cumin for 35 days. After anesthetizing the mice, their adipose tissue was collected. Total RNA was extracted, and after the qualification by agarose gel electrophoresis, cDNA was synthesized. The expression changes of Leptin, AdipoQ, and PPARG genes were measured by real-time RT-PCR. In addition, adipose tissue and cell size were analyzed using the Oil Red O staining method and quantitation using Image J software. Finally, GraphPad prisim 9.0 was applied to statistically evaluate the cell size difference and gene expression changes. The results of this study showed a significant decrease in Leptin gene expression levels (FC=0.42, Sig.=0.00, P<0.05) and also a significant increase in the expression of AdipoQ and PPARG (FC=1.8, Sig.=0.00, P<0.05) genes in adipose tissue in the treated group compared with the control group. Also, a considerable decrease in adipose tissue cell size in the treatment group was observed (210/520, Sig.=0.00, P<0.05). The results of this study are supported by similar studies and confirmed that the compounds in black cumin can be useful in preventing abnormal fat storage and problems such as metabolic syndromes by modulating the cellular metabolism of lipids.